Contingent preference for flexibility: eliciting beliefs from behavior - Philipp Sadowski (Theoretical Economics, 2013)
Following Kreps (1979), I consider a decision maker who is uncertain about her future taste. This uncertainty leaves the decision maker with a preference for flexibility: When choosing among menus containing alternatives for future choice, she weakly prefers menus with additional alternatives. Standard representations accommodating this choice pattern cannot distinguish tastes (indexed by a subjective state space) and beliefs (a probability measure over the subjective states) as different concepts. I allow choice between menus to depend on objective states. My axioms provide a representation that uniquely identifies beliefs, provided objective states are sufficiently relevant for choice. I suggest this result as a choice theoretic foundation for the assumption, commonly made in the (incomplete) contracting literature, that contracting parties who know each others' ranking of contracts, also share beliefs about each others' future tastes in the face of unforeseen contingencies.
Keywords: D01; D81; D82; D83; D86; 330; Preference for flexibility; unique beliefs; unforeseen contingencies; incomplete contracts